2008
DOI: 10.1016/j.exger.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Very small embryonic-like (VSEL) stem cells in adult organs and their potential role in rejuvenation of tissues and longevity

Abstract: Recently, we purified rare CXC chemokine receptor 4 expressing (CXCR4 + ) small stem cells (SCs) from the murine bone marrow (BM) that express markers characteristic for embryonic (E)SCs, epiblast (EP)SCs, and primordial germ cells (PGCs). We named these primitive cells very small embryonic-like (VSEL) SCs (VSELs). Our data indicate that VSELs are also present in many other organs in mice and that they may differentiate into cells from all three germ layers. Similar SCs were also isolated from human cord blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 50 publications
4
65
1
Order By: Relevance
“…4E), indicating their transformation to a differentiating status. Previous investigations showed that Vasa-positive VSEL stem cells isolated from adult organs express several characteristic markers of early PGCs, including fetal-type alkaline phosphatase, Oct4, SSEA-1, CXCR4, Stella, Fragilis, Nobox and Hdac6 (Ratajczak et al, 2008). Because the porcine PSCs described herein similarly express a number of typical, early PGC markers (Figs 2 and 4), these findings might indicate a close association of PSCs with Vasa-positive VSELs and epiblast-derived PGCs.…”
Section: Pscs Share Characteristics With Epiblast-derived Pgcsmentioning
confidence: 56%
See 1 more Smart Citation
“…4E), indicating their transformation to a differentiating status. Previous investigations showed that Vasa-positive VSEL stem cells isolated from adult organs express several characteristic markers of early PGCs, including fetal-type alkaline phosphatase, Oct4, SSEA-1, CXCR4, Stella, Fragilis, Nobox and Hdac6 (Ratajczak et al, 2008). Because the porcine PSCs described herein similarly express a number of typical, early PGC markers (Figs 2 and 4), these findings might indicate a close association of PSCs with Vasa-positive VSELs and epiblast-derived PGCs.…”
Section: Pscs Share Characteristics With Epiblast-derived Pgcsmentioning
confidence: 56%
“…These cells expressed early primordial germ cell (PGC) markers, including OCT4 (POU5F1), NANOG and SOX2 (Virant-Klun et al, 2008). The isolated PGCs were similar to cells termed 'very small embryonic-like (VSEL) stem cells', which have been found in a number of human and other animal adult tissues (Ratajczak et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…Especially, not only a number of these cells in adult organs decreases with the age but also their ability to form spheres containing VSEL-DS declaims with time. Whereas, a number of monopotent hemato/lymphopoiesis committed HSC increase in older animals [40,41].This age-dependent content and ability of VSELs in adult organs may explain that these cells could play a pivotal role in the normal cell turn over and the life span control of mammals.Moreover, a significantly higher number of VSELs in long-living murine strains (e.g., Laron dwarfs and Ames dwarfs), whose longevity is explained by low levels of circulating IGF1 and a decrease in IIS. By contrast, the number of VSELs is reduced in mice with high levels of circulating IGF1 and enhanced IIS (e.g., growth hormone-overexpressing transgenic mice) compared to normally aging littermates [42,43].…”
Section: Special Potency and Hypothesized Role Of Vselsmentioning
confidence: 99%
“…Thus, VSELs may be progeny of epiblast cells to develope tissues and a reserve pool of PSCs to repair tissue. Furthermore, the quiescent state of VSELs may also be a physiological protective mechanism of preventing uncontrolled proliferation, tumor formation [28]. Furthermore, The bone-forming activity of VSELs, exceeded the activity of other populations of BM-purified cells tested in the same assay if embedded in gelatin sponges and implanted into living mice.…”
Section: Special Potency and Hypothesized Role Of Vselsmentioning
confidence: 99%
See 1 more Smart Citation